Analisa Kinerja SMP K Satu Bakti Bogor - Manurung, Darwin; Baga, Lukman M.; Krisnatuti, Diah (Jurnal Manajemen dan Organisasi, 2015)
Good performance results are very valuable promotion for the progress of a private junior high school, either at the provincial or regional level. The implementation of regional autonomy has implications for the implementation of the evaluation process to be more professional, objective, honest and transparent as a series of school supervision and guidance. In order to improve the quality of education, there is a need tochange the supervision system functioning not only as a monitor but also guidance to organize education. Analysis process of all aspects of education should be directed at efforts to ensure the implementation of quality education (Quality Assurance) and empower those evaluated so as to produce graduates in accordance with established standards. Each school performance analyzed is expected to have positive impacts for the community, especially to any parents who want to send their children to junior high school, especially SMPK Satu Bakti Bogor. Although there are a few schools established for quite a long time and there are some newly operating, it is not a guarantee for these private junior high schools to continue to grow. This has encouraged the school component to perform better and have special attractions. Some of the private schools in Bogor city have been experiencing problems similar those in the SMP K Satu Bakti; namely, the difficulty to attract new students to enroll in their school. A better quality of performance, accordingly is required in order to attract more qualified applicants and prospective students in the future which is expected to maintain the sustainability of this junior high school existance. Keywords: performance, consumer interest, importance of performance analysis, analytical hierarchy process